Risk factors associated with breast cancer patients in Teresina, Piauí (Brazil) - Fabrício Ibiapina Tapety; Juliana Veloso Magalhães; Francisco José de Almeida Cruz Júnior; Lucas do Vale Teixeira Cunha; Tatiana Vieira Souza Chaves; Ana Amélia de Carvalho Melo Cavalcante (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: To characterize the risk factors for breast cancer in patients seen in a referral center in the city of Teresina, Piaui (2010-2012). Methods: A descriptive exploratory study with 197 patient records. A personal health questionnaire was administered to 20 patients and 20 women without breast cancer. The data were submitted to SPSS 13.0 for analysis of percentages, means and Spearman correlations. Results: The average age (55 years) was positively correlated with ductal carcinoma (83%) and 10% of metastases. The occupation of domestic, family history, medications, and exposure to ionizing radiation have been demonstrated as risk factors. Significant (p <0.001) positive correlation (r = 0.6642, p = 0.002) were observed between breast cancer family history and occupation. Conclusion: Prevention strategies related to environmental, occupational and hereditary factors are necessary to minimize the risk of mutagenicity and carcinogenicity. Descriptors: Breast cancer, Risk factors, Mutagenicity.